Mbayu’s Model of Patriotism: Integrating Sports, Academia, and Socio-Cultural Influences (African Journal for Industrial and Applied Mathematics, 2025)
Patriotism is a changing, complex force inside a nation, whose manifestations are determined by factors as diverse as success in sports, scientific discoveries, cultural pride, economic development, and the presence of national heroes.This study develops a generalized mathematical model for patriotism as the sum ofthese effects, both emotional and enduring. In particular, the model records surgesin patriotism after major sporting victories due to the transience of these surges, forinstance, after the victory of the Indomitable Lions or the boxing exploits of Francis Ngannou. In contrast, the model also underlines the long-lasting characteristicsof patriotism shaped by scientific progress, such as a Cameroonian being rankedhigh in mathematics, cultural legacy, infrastructure expansions, and economic development. The sports effect is a series of ephemeral spikes in patriotic sentimenttriggered by importance and emotional resonance. In contrast, both the science andinfrastructure effects are slowly cumulative processes that build a longer foundation of national pride. These effects, alone and in combination, are shown in thevisualizations of their contributions to patriotism over time. This work emphasizesthe importance of acknowledging and effectively harnessing these myriad influences for a strong, cohesive nation. The insights are actionable, helping leaders tostimulate a rational yet productive sense of patriotism that is engaged with nationaldevelopment, starting with emotional stimuli but progressing to more permanentinvestments.
Keywords: Mathematical models; patriotism; emotional patriotism; enduring patriotism; sports achievements; scientific advancements; infrastructure development; cultural heritage; economic growth; national unity.